PERANCANGAN DAN IMPLEMENTASI JARINGAN VPN DENGAN METODE L2TP/SSTP PADA PT PALAPA MEDIA INDONESIA - Muhamad Fazar Riansah (CV. Multi Kreasi Media, 2024)
Internet has become an important requirement for communication. Using the internet makes it easier for someone to get information anytime and anywhere. The Internet is also used in local networks. Virtual Private Network (VPN) allows devices outside of the local network to be connected to a public network anywhere, provided that the device is connected to the internet. Therefore, in this journal a VPN network is designed with the L2TP and SSTP methods using a MikroTik router. and increase data security in the network.